What is the core essence of small city boutique hotels? - Loureiro, S. M. C. (2020)
Purpose: The purpose of this study is to contribute with new insights into the nature, dimensionality and measurement of the core essence of the small city boutique hotel (SCBH), something which has been limited in the literature to date. It further explores the conceptual relationships of SCBH with other constructs, providing greater understanding of the nature of these specific conceptual associations and showing that the SCBH scale exhibits construct validity. Design/methodology/approach: This study followed the Churchill’s paradigm to methodologically design the study and develop the scale. Based on an exploratory qualitative inquiry (one focus group and ten interviews) and quantitative assessment (two surveys), support was found for a three-dimensional scale. Findings: Results support the proposed measures of the scale (dream, hospitality and style) in terms of construct, convergent, discriminate, nomological and predictive validity. The findings also suggest that while authenticity acts as a SCBH antecedent, pleasant arousal and preference represent SCBH consequences. Originality/value: By developing and validating a SCBH scale for city destination, this study addresses an identified literature gap. Specifically, it conceptualizes SCBH as guests’ perception about core characteristics of SCBHs located in the city.